Does Work Engagement Explain Job Characteristics and Job Satisfaction in Rural Education? - Meiske Claudia; Muhammad Fahrin Noor; Nasywa Ghaida Salsabila; Megi Nediawan (Lembaga Bale Literasi, 2026)
Teacher job satisfaction is important for educational quality, yet the mechanism linking job characteristics and satisfaction remains underexplored in elementary schools. This study analyzes the effects of job demands and job resources on job satisfaction, with work engagement as a mediator among educators in Haruyan District, South Kalimantan. A quantitative survey was conducted with 120 educators selected from 228 teachers in 24 public elementary schools using proportionate stratified random sampling. Responses were measured using a Likert-scale questionnaires and analyzed through PLS-SEM with the disjoint two-stage approach in SmartPLS 4. The results show that job demands and job resources do not directly affect job satisfaction. However, job demands positively affect work engagement, job resources strongly affect work engagement, and work engagement positively affects job satisfaction. Work engagement fully mediates both relationships. These findings indicate that teacher satisfaction is primarily shaped through psychological engagement. Moderate demands function as challenge demands, while resources strengthen motivation through support, feedback, coaching, and development opportunities.